Síntese, caracterização e aplicação biológica de hidroxiapatita: em presença de gelatina e associada a sulfato de gentamicina - Ferreira, Fernando Ribeiro (2009)
The use of biomaterials comes from old times and recently bioceramics have been deeply investigated as a source of material for bone implant. Amongst the different biomaterials, hydroxyapatite (HA) has great importance for being one of the compounds which forms the bone mineral phase. Therefore, HA has been largely studied, mainly due to the fact that it is a bioactive compound. Calcium phosphate synthesis via precipitation presents great advantages such as low cost and simplicity, but most procedures described in literature regard the formation of non stoichiometric products and phase mixture. This work studied the HA synthesis by analyzing the influence of gelatin concentration in the precipitation means on the characteristics of the hydroxyapatite obtained. Gentamicin was also incorporated to the HA samples and antimicrobial activity was analyzed. The hydroxyapatite was obtained through precipitation in aqueous and gelatin means, being later on dried, sieved and calcined at 700ºC. Gelatin concentrations of 1, 6, 10 and 60 g.L-1 were used. Then, gentamicin sulfate was added, 1% in mass. Samples were characterized through Xray diffraction, specific superficial area through the BET method, thermal analysis, infrared spectroscopy and transmission and scanning electronic microscopy. The Xray diffraction revealed the presence of HA phase in all samples; and by refining through the Rietveld method, it could be seen, in the gelatin free sample, the presence of calcium carbonate and pure HA, for the sample prepared in gelatin, indicating that the presence of gelatin made the hydroxyapatite phase stable. XRF and EDS indicated that Ca/P ratio was slightly above what had been expected to obtain stoichiometric hydroxyapatite. The granulometric distribution analysis and superficial area through the BET method indicated differences in the average size of agglomerates and the superficial area of the material in relation to the synthesis and samples preparation process to receive the antibiotic, which was processed through milling in a ball mill. SEM and TEM revealed morphological and structural aspects characteristic of the hydroxyapatite with the formation of nanometric crystal agglomerates. Samples microbial activity evaluation with human saliva showed that pure HA has the effect of inhibiting microbial growth; CFU counting was observed to reduce. For the samples with antibiotic there was a CFU equal zero proving that the process used for gentamicin incorporation to the HA kept the antibiotic property of the material, and that the same was released during the tests.